Stakeholders' Perception on Influence of Insurgencies on Pupils’ Enrollment and Achievement of Quality Primary Education in Selected Educational Zones in Katsina State, Nigeria - Kafur, Lubabatu Suleiman; Sheidu, Haruna; Abbas, Habiba (Journal of Innovation in Education and Social Research, 2024)
Insurgencies has greatly affected several sectors of Nigerian economy such as Agriculture, health, commerce and most especially educational sector that is the foundation upon which other sectors is built. The level of pupils’ enrolment and attainment of quality education in Katsina State over the years is significantly declining due to several factors like unqualified teachers recruitment, poor funding to education, poor welfare of teachers and most especially impact of insurgencies. The researchers therefore feel deeply worried to carry out this research work titled “Stakeholders’ perception on influence of insurgencies on primary school pupils’ enrolment and achievement of quality education in selected educational zone in Katsina state, Nigeria” aimed at addressing the causes and impact of insurgencies in Nigeria with emphasis in Katsina State. The study adopt survey research design. The target population is all the teachers and head teachers from Katsina and Dutsin-ma educational Zones respectively. The study used structured questionnaires for gathering data while descriptive and inferential statistics was used to analyze data collected and answer research questions. The study reveal that insurgency have affected primary school enrollment of children and attainment of quality education. It was recommended that acquiring entrepreneurship skills education after graduation will enable young graduate to be self-employed without waiting for white collar job or join bad wagon of terrorists after graduation, improved security measures Such as installation of surveillance cameras as well as posting of adequate personnel should be posted around school environment to avert insurgency attacks and adequate funding should be allocated to education sector as recommended by UNESCO at both national and state level to cater for teachers’ training and welfare to enable them put in their best by giving the pupils desired quality education.